2017
DOI: 10.1002/hed.24758
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of venous thromboembolism in otolaryngology–head and neck surgery

Abstract: Chemoprophylaxis may not be necessary in the OHNS non-SCC or free flap patient population and must be balanced against an increased risk of bleeding. © 2017 Wiley Periodicals, Inc. Head Neck 39: 1249-1258, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
63
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 35 publications
(44 reference statements)
4
63
1
Order By: Relevance
“…VTE as a disease entity includes both deep vein thrombosis (DVT) and pulmonary embolism (PE). Although the incidence of VTE in the general otolaryngology population is low, 1–5 the incidence in patients with cancer has been reported to be higher at 1.4% - 5.8%. 5, 6 This higher incidence rate of VTE in HNC patients is likely due to older age, tobacco use, major surgery, reduced mobility, and malignancy itself.…”
Section: Introductionmentioning
confidence: 99%
“…VTE as a disease entity includes both deep vein thrombosis (DVT) and pulmonary embolism (PE). Although the incidence of VTE in the general otolaryngology population is low, 1–5 the incidence in patients with cancer has been reported to be higher at 1.4% - 5.8%. 5, 6 This higher incidence rate of VTE in HNC patients is likely due to older age, tobacco use, major surgery, reduced mobility, and malignancy itself.…”
Section: Introductionmentioning
confidence: 99%
“…First, 7 of 23 studies in their meta-analysis include rates of VTE from both outpatient and inpatient surgery. 1 The primary questions that arise with VTE prevention surround inpatient prevention as VTE occurs at a 150-fold greater rate in hospitalized patients. 4 Including ambulatory surgery patients in their study limits the generalizability of their findings and may underestimate the observed incidence of VTE.…”
mentioning
confidence: 99%
“…Nine of the 23 studies were limited to specific subpopulations comprising outpatient thyroidectomy, outpatient parathyroidectomy, epistaxis, acoustic neuroma surgery, pituitary surgery, or laryngectomy. 1 Third, the authors suggest that only patients who undergo OHNS with either squamous cell carcinoma or free flap surgery and with risk factors for VTE require chemoprophylaxis. However, analysis of the 4 studies that use the Caprini risk stratification, a validated tool to select patients at highrisk for VTE, offers worthwhile insights.…”
mentioning
confidence: 99%
“…2 Second, heterogeneity in our included studies was a priori expected to be high due to inclusion of different patient populations. 3 This was thoroughly addressed and discussed in the methods, results, and discussion sections. 3 The third point is unfortunately a common misconception.…”
mentioning
confidence: 99%
“…3 This was thoroughly addressed and discussed in the methods, results, and discussion sections. 3 The third point is unfortunately a common misconception. The 2012 CHEST guidelines do not state that OHNS data is similar to plastic and reconstructive surgery (PRS) data, and this is not proven in any literature, to the best of our knowledge.…”
mentioning
confidence: 99%